SYNTHESIS, CHARACTERIZATION, DNA CLEAVAGE AND ANTIMICROBIAL ACTIVITIES OF SCHIFF BASE LIGAND DERIVED FROM 5-CHLORO-3-PHENYL-1H-INDOLE-2-CARBOXYHYDRAZIDE AND O-VANILLIN AND ITS METAL (II) COMPLEXES - Udayagiri, Mahadev Dhanraj; Yernale, Nagesh Gunvanthrao; Mruthyunjayaswamy, Bennikallu Hire Mathada (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: The main objective of the present work was to synthesize a new Schiff base ligand 5-chloro-N'-(2-hydroxy-3-methoxybenzylidene)-3-phenyl-1H-indole-2-carbohydrazide and its Cu (II), Co (II), Ni (II) and Zn (II) complexes and study their biological activity. Methods: The compounds are characterized by elemental analysis and various physicochemical techniques like IR, 1H NMR, ESI-mass, UV-Visible, TGA analyzes and molar conductance data. All the compounds were screened for their antibacterial and antifungal activity by MIC method. Further, antioxidant activity was performed by using 2,2-diphenyl-1-picryl-hydrazyl (DPPH) and DNA cleavage activity by Agarose Gel Electrophoresis (AGE) method. Results: Spectral investigations suggested octahedral coordination geometrical arrangement for all the metal (II) complexes, having 1:2 stoichiometric ratio of the type [M(L)2]. The antimicrobial activity results revealed that the metal complexes were found to be more active than the free ligand. Furthermore, the DNA cleavage activity of the compounds on plasmid DNA pBR322 molecule showed moderate activity. Conclusion: The newly synthesized ligand acts as ONO donor tridentate chelate and coordinated through an oxygen atom of carbonyl function, azomethine nitrogen and phenolic oxygen atom to the Cu, Co, Ni and Zn metal ions and form octahedral geometrical arrangement. All the complexes are found to be non-electrolytic in nature. Further, all the newly prepared compounds showed moderate biological activity. Keywords: Indole, o-Vanillin, Transition metal complexes, Powder XRD, ESR, DNA cleavage Antimicrobial, Antioxidant Â